Analisis Pelaksanaan Elektronik Government Sebagai Upaya Mewujudkan Tata Kelola Pemerintahan Yang Baik (Good Governance) - Rahmat Muhajir; Abdurrahman Abdurrahman; Hidayatullah Hidayatullah (Journal Law and Government, 2024)
In the current era of digitalization and modernization, the development of information technology (IT), especially computer technology and internet networks is increasingly rapid, one way that can be used by the government to realize good governance. Based on the Presidential Instruction of the Republic of Indonesia Number 3 of 2003 concerning National Policy and Strategy for the Development of E-Government and also the Regional Regulation of the Province of West Nusa Tenggara Number 3 of 2018 concerning Electronic System-Based Government Governance, government agencies should implement electronic-based government services and administration. The purpose of the study was to determine how the implementation of electronic government is as an effort to realize good governance in the Social Service of West Nusa Tenggara Province, and to determine what factors influence the implementation of electronic government as an effort to realize good governance in the Social Service of West Nusa Tenggara Province. The type of research used is a qualitative descriptive research type. Based on the results of the study and discussion, it can be concluded that: (1). Of the three forms of implementation of the theory of electronic government implementation forms according to Indirajit, namely publish, interact and transact, only 2 forms are applied, namely publish and interact, while the third form, namely the transact form, is not applied by the NTB social service.